O dilema do compliance nas relações de trabalho : entre normas e necessidades humanas - Jesus, Joéverton Silva de (2024)
This study aims to explore the dilemma between human relations, the law and the economy, assessing how labor compliance influences labor interactions in our country. We seek to understand how labor compliance relates to private autonomy and the principles of worker protection, while at the same time creating an environment where risks are known, monitored and mitigated. To this end, we examine the legal nature of labor compliance and its practical impacts on labor relations, as well as analyzing its role in the self-regulation of human relations. Our aim is not to defend compliance unconditionally, but to offer an approach for study and analysis, identifying the legal divergences and convergences for effective implementation. We consider the nuances between will and necessity, seeking to value the worker in harmony with the efficiency of productive relations. We discuss the uncertainties related to the effectiveness of labor compliance and possible solutions, adopting a multidisciplinary approach that enriches the discussion on how to promote healthy relationships in the workplace, not only in legal terms, but also in ethical and psychological terms, considering the complexities of human will and intrinsic needs.